Does antiretroviral treatment change HIV-1 codon usage patterns in its genes: a preliminary bioinformatics study - Palanisamy, Navaneethan (AIDS research and therapy, 2017)
Background Codon usage bias has been described for various organisms and is thought to contribute to the regulation of numerous biological processes including viral infections. HIV-1 codon usage has been previously shown to be different from that of other viruses and man. It is evident that the antiretroviral drugs used to restrict HIV-1 replication also select for resistance variants. We wanted to test whether codon frequencies in HIV-1 sequences from treatment-experienced patients differ from those of treatment-naive individuals due to drug pressure affecting codon usage bias.Results We developed a JavaScript to determine the codon frequencies of aligned nucleotide sequences. Irrespective of subtypes, using HIV-1 pol sequences from 532 treatment-naive and 52 treatment-experienced individuals, we found that pol sequences from treatment-experienced patients had significantly increased AGA (arginine; p = 0.0002***) and GGU (glycine; p = 0.0001***), and decreased AGG (arginine; p = 0.0001***) codon frequencies. The same pattern was not observed when subtypes B and C sequences were analyzed separately. Additionally, irrespective of subtypes, using HIV-1 gag sequences from 524 treatment-naive and 54 treatment-experienced individuals, gag sequences from treatment-experienced patients had significantly increased CUA (leucine; p < 0.0001***), CAG (glutamine; p = 0.0006***), AUC (isoleucine; p < 0.0001***) and UCU (serine; p = 0.0005***), and decreased AUA (isoleucine; p = 0.0003***) and CAA (glutamine; p = 0.0006***) codon frequencies.Conclusion Using pol and gag genes derived from the same HIV-1 genome, we show that antiretroviral therapy changed certain HIV-1 codon frequencies in a subtype specific way.